Enhancing Fatigue Performance of Sandwich Composites with Nanophased Core. (7th June 2010) - Zainuddin, S.; Mahfuz, H.; Jeelani, S.
Abstract : We report fatigue performance of sandwich composites with nanophased core under shear load. Nanophased core was made from polyurethane foam dispersed with carbon nanofiber (CNF). CNFs were dispersed into part-A of liquid polyurethane through a sonication process and the loading of nanoparticles was 1.0 wt%. After dispersion, part-A was mixed with part-B, cast into a mold, and allowed to cure. Nanophased foam was then used to fabricate sandwich composites. Static shear tests revealed that strength and modulus of nanophased foams were 33% and 19% higher than those of unreinforced (neat) foams. Next, shear fatigue tests were conducted at a frequency of 3 Hz and stress ratio (R) of 0.1. S-N curves were generated and fatigue performances were compared. Number of cycles to failure for nanophased sandwich was significantly higher than that of the neat ones. For example, at 57% of ultimate shear strength, nanophased sandwich would survive 400, 000 cycles more than its neat counterpart. SEM micrographs indicated stronger cell structures with nanophased foams. These stronger cells strengthened the sub-interface zones underneath the actual core-skin interface. High toughness of the sub-interface layer delayed initiation of fatigue cracks and thereby increased the fatigue life of nanophased sandwich composites.